Career and Life Role Aspirations of High Ability Women Graduates - McBain, Laura-Lynne; Woolsey, Lorette K. (Canadian Journal of Counselling and Psychotherapy, 2011)
This exploratory and descriptive study used a biodemographical questionnaire and a variant of Kelly's (1955) repertory grid technique to examine the life role aspirations (career, home and family, and personal) of a group of high ability women undergraduates. The results showed that these women aspired to relatively high level full-time careers for the next fiveyear period of their lives. Their most preferred roles were professional roles. They appeared to be most strongly influenced by a desire for personal growth, which they seemed to construe mostly in terms of achievement. On the whole, they seemed to be conflict-free in their attitudes toward their projected life roles. The data support more recent theory on the diminishing importance of the career-marriage conflict for women. The results of this study are useful to counsellors and educators working with high ability women who are seeking to combine multiple roles in a manner which allows for maximum development of potential.